Pengaruh Penggunaan Media Pembelajaran CS3 Berbasis Android Terhadap Kemampuan Berpikir Geometris Siswa SDN 01 Benteng Pasar Atas Bukittinggi - Oneika, Sri Esa; Masniladevi, Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study was to determine the effect of using android-based CS3 learning media on students' geometric thinking abilities. This research is a pre-experimental research, using One Group Pretest and Posttest. The population was all students of class IV SDN 01 BentengPasarAtas, Bukittinggi. The sampling technique is the Totally sampling technique. The sample consisted of 24 Digital class students who were learning to use Android. Data collection techniques are test instruments. The instrument used was an objective test with HOTS-based questions on extensive learning material and the circumference of flat structures that had been validated by experts. Data were analyzed using t-test. Obtained results t count = 15.473 and t table = 2.064. So that t arithmetic> T table H0 is rejected and Ha is accepted. The conclusion of this study is the use of CS3 learning media based on android on broad material and the circumference of flat shape can affect student mathematics learning outcomes.